S100A9-RAGE axis accelerates formation of macrophage-mediated extracellular vesicle microcalcification in diabetes - Kawakami, Ryo (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: Vascular calcification is a cardiovascular risk factor and accelerated in diabetes. Previous work has established a role for calcification-prone extracellular vesicles (EVs) in promoting vascular calcification. However, the mechanisms by which diabetes provokes cardiovascular events remain incompletely understood. Our goal was to identify that increased S100A9 promotes the release of calcification-prone EVs from human macrophages in diabetes. APPROACH AND RESULTS: Human primary macrophages exposed to high glucose (25mmol/L) increased S100A9 secretion and the expression of receptor for advanced glycation end products (RAGE) protein. Recombinant S100A9 induced the expression of pro-inflammatory and osteogenic factors, as well as the number of EVs with high calcific potential (alkaline phosphatase activity, p<0.001) in macrophages. Treatment with a RAGE antagonist or silencing with S100A9 siRNA in macrophages abolished these responses, suggesting that stimulation of the S100A9-RAGE axis by hyperglycemia favors a pro-calcific environment. We further showed that an imbalance between nuclear factor-2 erythroid related factor-2 (Nrf2) and NF-κB pathways contributes to macrophage activation and promotes a pro-calcific environment. In addition, streptozotocin-induced diabetic Apoe(−/−)S100a9(−/−) mice and mice treated with S100a9 siRNA encapsulated in macrophage-targeted lipid nanoparticles (LNPs) showed decreased inflammation and microcalcification in atherosclerotic plaques, as gauged by molecular imaging and comprehensive histological analysis. In human carotid plaques, comparative proteomics in diabetic patients and histological analysis showed that the S100A9-RAGE axis associates with osteogenic activity and the formation of microcalcification. CONCLUSIONS: Under hyperglycemic conditions, macrophages release calcific EVs through mechanisms involving the S100A9-RAGE axis, thus contributing to the formation of microcalcification within plaques.